Are platinum nanoparticles safe to human health? - Ewelina Czubacka; Sławomir Czerczak (Medycyna Pracy, 2019)
Platinum nanoparticles (PtNPs) have been widely used not only in industry, but above all in medicine and diagnostics. However, there are disturbing reports related to the toxic effects of nanoplatinum, which is the main reason why the authors of this study have decided to review and analyze literature data related to its toxicity and impact on human health. While PtNPs may be absorbed by the respiratory and digestive tract, and can penetrate through the epidermis, there is no evidence concerning their absorption through the skin. Platinum nanoparticles accumulate mainly in the liver and spleen although they also reach other internal organs, such as lungs, kidneys or heart. Toxicokinetics of platinum nanoparticles depends strongly on the particle size. Only few studies regarding platinum nanoparticles toxicity have been conducted. Animals intratracheally exposed to platinum nanoparticles have demonstrated an increased level of proinflammatory cytokines in bronchoalveolar lavage which confirms inflammatory response in the lungs. Oral administration of PtNPs can cause inflammatory response and induce oxidative stress. Nanoplatinum has been found to induce hepatotoxicity and nephrotoxicity via the intravenous route. It can cause DNA damage and cellular apoptosis without significant cytotoxicity. There are no research studies on its carcinogenicity. Fetal or maternal toxicity has not been observed, but an increased mortality and a decreased growth of the offspring have been demonstrated. Platinum nanoparticles may permeate the skin barrier but there is no evidence for their absorption. Due to the insufficient number of tests that have been carried out to date, it is not possible to clearly determine the occupational exposure limit value; however, caution is recommended to employees exposed to their effects. Med Pr. 2019;70(4):487–95